2022
DOI: 10.22219/jes.v7i1.17012
|View full text |Cite
|
Sign up to set email alerts
|

The Determinant of Product Advantage, Customer Experience and Trust on the Reputation of Bank Syariah Indonesia Post-Merger at Surakarta City

Abstract: This study aims to determine the impact of product advantage, customer experience and trust on the reputation of Bank Syariah Indonesia post-merger at Surakarta City. This research was quantitative with data analysis techniques using multiple linear regression. The sampling technique in this study was purposive sampling with certain criteria. The respondent in this study were 100 customers of Bank Syariah Indonesia at Surakarta City. The result found that product advantage has a positive and significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…H 2 result revealed that CEx significantly and positively influences CR (β=0.855, T=47.149, p=0.000), so H 2 was accepted (see Table 5). (Abdullah, 2022) conducted a study in Indonesia that provided the same results. Results indicated that Corporate Reputation impacted by customer experience; trust is an essential element in the banking sector.…”
Section: Structural Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…H 2 result revealed that CEx significantly and positively influences CR (β=0.855, T=47.149, p=0.000), so H 2 was accepted (see Table 5). (Abdullah, 2022) conducted a study in Indonesia that provided the same results. Results indicated that Corporate Reputation impacted by customer experience; trust is an essential element in the banking sector.…”
Section: Structural Modelmentioning
confidence: 89%
“…CEx, trust, and product advantages have a positive impact on CR (Abdullah, 2022). (Choi et al, 2022) checked the relationship between CR (customer-based) and customer engagement behavior with mediating effect of brand love and customer identification and the moderating effect of industry type.…”
Section: Customer Experience and Corporate Reputationmentioning
confidence: 99%
“…Another study conducted in Pakistan found that customer experience, analyzed through factors like environment assessment, moments of truth, frontline staff, and product offerings, significantly and positively influences corporate reputation and word of mouth (Fida et al, 2023). Similarly, a study in Indonesia focused on the banking sector and found a positive and significant relationship between customer experience and bank reputation, with product advantage and trust also contributing to reputation (Abdullah, 2022).…”
Section: Relation Between Student Experience and University Reputationmentioning
confidence: 99%